Exercícios no tratamento do linfedema e a interferência sinérgica do mecanismo de compressão quanto à sua correta colocação - Barufi, Stelamarys (2018)
Lymphedema is a specific type of edema resulting from an accumulation of macromolecules caused by dynamic or mechanical changes of the lymphatic system. Worldwide it is the second greatest cause of disability to work for medical reasons, but there is a lack of clinical studies in specific areas to support and providing treatment. There is no consensus of a single approach to the treatment of lymphedema but an association of therapies is suggested. Of the different approaches, exercising associated with a compression mechanism is one option used to reduce the lymphedema. Objective: The objective of this study was to compare the effect on the reduction of lower limb volume of walking under three different circumstances: using a well-adjusted grosgrain stocking, a badly adjusted grosgrain stocking and without any stocking. Methods: A randomized crossover study was performed to evaluate the efficacy of a correctly adjusted grosgrain stocking to reduce limb volume. Fourteen female and three male patients with ages ranging between 21 and 68 years (mean age: 45.6 years) and a clinical diagnosis of unilateral lower limb lymphedema due to congenital or secondary causes were enrolled in the Clinica Godoy in São Jose do Rio Preto. The assessment of leg size was achieved by volumetry using the water displacement technique before and immediately after each intervention of the experiment. Patients were submitted to three interventions, one per week: 1) a one-hour walk with a well-adjusted grosgrain stocking; 2) a one-hour walk without adjusting the grosgrain stocking; 3) a one-hour walk without using any stocking. After performing volumetry on arrival at the clinic, a draw was carried out using sealed envelopes to define the sequence of the interventions for each patient (well-adjusted stocking, badly adjusted stocking or no stocking). The assessment of correctly fitting stockings, when necessary, was carried out by a trained physiotherapist. The paired t test was used for statistical analysis with an alpha error of 5% being considered acceptable. Results: A mean reduction of -46.29 mL (standard deviation: 42.46) in limb volume was achieved with the well-adjusted stocking with volume reductions occurring in 14 patients and an increase in volume in three (p-value <0.002). The limb volume increased by a mean of 74.8 mL (standard deviation: 99.75) when the patients walked for one hour without any constrain mechanism (p-value <0.007). When walking with unadjusted socks, the mean increase in volume of 33.5 mL was not statistically significant (p-value <0.14). In the descriptive analysis, the volumetric variations were significantly different between the three situations (adjusted stockings, stockings without adjustment and without stockings) (p-value = 0.0002). On comparing the reductions in edema with adjusted and unadjusted stockings, the reduction was greater when they were well-adjusted (p-value = 0.0008). However, there was no significant difference between unadjusted stockings and when the patients walked without stockings (p-value = 0.07). Conclusion: The constant adjustment of non-elastic constraint mechanisms in the treatment of lymphedema has a synergistic effect on the reduction of limb volume. The use of a grosgrain stocking leads to a reduction in limb volume when associated to walking, and walking without a stocking results in an increase in the volume of the lymphedematous limb.